Geoturismo: uma proposta de turismo sustentável e conservacionista para a Região Nordeste do Brasil / Geotourism: a proposal for conservation and sustainable tourism for the Northeast Region of Brazil - Marcelo Martins Moura-Fé (Sociedade & Natureza)
Geotourism is presented as a promising segment of tourism, ecotourism related with specific and essential to the conservation of geodiversity, in line with many precepts required for local economic development community features. The aim of this study is to analyze the geotourism and its fundamental precepts and applicable to the development of sustainable tourism and nature conservation in the Northeast region of Brazil, contemplating the strategic dimensions of this activity in the short, medium and long term - the interpretation of the landscape and promoting environmental education, as well as actual and potential examples of your existing deployment in the Northeast region. Geotourism, along with the other branches of sustainable tourism, appears as a real alternative for the development of the Northeast region and to improve the living conditions of local populations, since their implementation will take under conditions of efforts and investments. In addition, another policy of tourism development, an activity beyond the northeastern coast, fostering the development of the interior regions of the states, the municipalities in rural areas, contributing to greater regional integration is necessary.